Esthetic Rehabilitation of Bilateral Geminated Teeth: A Case Report - Türkaslan, Süha; Gökçe, Hasan Suat; Dalkız, Mehmet (European Journal of Dentistry, 2007)
Geminated teeth are the consequences of developmental anomalies leading to the eruption of joined elements. According to current definitions, gemination occurs when one tooth bud tries to divide, while fusion occurs if two buds unite. Clinical experience shows, however that diagnosis can be complicated due to superimposed anomalies. This report describes a unique case of bilateral gemination of permanent maxillary central incisors. The esthetic rehabilitation of the geminated incisors accomplished utilizing all ceramic crowns. It is important that in these types of cases, reaching to the available esthetics and avoiding the complication of caries and periodontal problems with prosthetic application is satisfactory. (Eur J Dent 2007;1:188-191)
Keywords: Gemination; Double teeth; Fusion; Permanent teeth; Developmental anomalies; Maxillary central incisors